97 Impact of Regionalized Forage Quality and Quantity and Feed Grain Water Use on the Daily Texas Beef Cattle Water Footprint and Supply Chain Efficiency. (28th November 2020) - Menendez, Hector M; Tedeschi, Luis O
Abstract: Livestock water use sustainability is a growing concern in the beef cattle sector. The Water Footprint Assessment (WFA) method has been used to quantify the water footprint (WF) of beef products but does not suggest any specific management strategies to decrease the WF of beef cattle (WFB) within and across the beef supply chain. The WFB is primarily influenced by forage and grain production water uses (m 3 /t), which are directly linked to dry matter (kg/d) and water intake (L/d) and cattle growth (kg/d). Therefore, the objective of this study was to assess the alteration of forage quality and above-ground biomass production (t/ha) of annual ryegrass (Lolium multiflorum) and bermudagrass (Cynodon dactylon), in addition to published WF estimates for corn (Zea mays) and soybean (Glycine max) production (m 3 /t) on the daily Texas WFB . A dynamic Texas Beef Water Footprint Model (TXWFB) was developed to predict WFB, using the System Dynamic methodology and equations from the Ruminant Nutrition System (RNS) and Beef Nutrient Requirements (NASEM) models. Results indicated that forage and crop biomass production is a high-leverage solution to offset the daily Texas WFB (%∆ = -55 to 130). The alteration of forage TDN had less of an impact on the Texas WFB (%∆ = -39 to 17). An ANOVA with a Tukey Posthoc test indicated that all WFB scenarios were significantly different (P < 0.05) except for the low versus base TDN under low water use conditions scenario. The variability in the use of green and blue waters for grains indicated that the final WFB, in the feedlot phase, may be lower than the WFB in the cow-calf or stocker stages under certain efficiency conditions. Identification of high and low-leverage solutions may help Texas cattle stakeholders implement systemic strategies that aid in the efforts for sustainable beef water use.